Male Erectile Dysfunction and Microalbuminuria in Adult Nigerians with Essential Hypertension - Busari, Olusegun Adesola (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Microalbuminuria has been described as a marker of generalized vascular damage. AIMS: The aim of the present study was to determine the prevalence of erectile dysfunction (ED) and microalbuminuria in adult male Nigerians with newly diagnosed hypertension. We also evaluated the relations between ED and microalbuminuria, electrocardiographic left ventricular hypertrophy, serum lipids, and cigarette smoking. MATERIALS AND METHODS: A total of 81 male adult Nigerians with newly diagnosed hypertension were recruited into the study. There were also 75 age- and sex-matched healthy normotensive controls. ED was evaluated using a standardized questionnaire of the International Index of Erectile Function and microalbuminuria was determined using the Micra Test strips (Boehringer Manneheim GMBh, Mannheim, Germany). RESULTS: Eighty-one hypertensive patients and 75 normotensive controls were studied. Mean age of the patients and the controls was 53.8 ± 5.6 and 51.2 ± 7.1 respectively. ED was found in 32.1% of the hypertensive patients and 16% of normotensive controls (P < 0.001). The prevalence of microalbuminuria was significantly higher in patients with ED than in those without it (65.4% vs. 23.6%, P < 0.0001). CONCLUSION: The study shows that ED and microalbuminuria are common in male adult Nigerians with hypertension. It also demonstrates that male ED is associated with an increased risk of cardiovascular disease.